Self-esteem as a mediator of the link between perfectionism and the impostor phenomenon. (1st December 2018) - Cokley, Kevin; Stone, Steven; Krueger, Nolan; Bailey, Marlon; Garba, Ramya; Hurst, Ashley
Abstract: Perfectionism has been linked to the impostor phenomenon; however, little is known about the underlying mechanisms of this relationship. Self-esteem was examined for its potential mediating role in the relationship between dimensions of perfectionism (e.g., discrepancy and standards) and the impostor phenomenon among 468 college students. Analyses indicated that self-esteem partially mediated the relationship between perfectionism and impostor feelings. Discrepancy had a positive direct and indirect effect on impostor feelings through the mechanism of self-esteem, while standards had a negative indirect effect on impostor feelings through the mechanism of self-esteem. Implications for enhancing self-esteem among students experiencing maladaptive perfectionism and impostor feelings are discussed.